Zero watermarking for medical images based on DFT and LFSR - Chunhua Dong; Jingbing Li; Yen-wei Chen; Yong Bai (2012 IEEE International Conference on Computer Science and Automation Engineering, 2012)
Medical images and data may encounter tampering, compromising patient's privacy and other safety issues in the process of storage and transmission of information. This paper proposes an algorithm of zero watermarking to address these issues using DFT. The algorithm avoids the sophisticated process of finding the Region of Non-Interest (RONI) of medical images, and uses a part of sign sequence of DFT coefficients as the feature vector of images for enhancing the robustness. Even if the algorithm is public, it can still withstand malicious attacks by using the private key to protect the medical image. Experimental result indicates that the watermarking scheme belongs to the blind watermarking extraction with strong robustness and invisibility to withstand rotation, scaling, translation, cropping and other attacks. Moreover, it can embed much more data compared with the existing watermarking techniques.